1996
DOI: 10.1007/bf02191829
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of theeapB andeapC genes ofCryphonectria parasitica encoding two new acid proteinases, and disruption ofeapC

Abstract: Two new proteinases secreted by Cryphonectria parasitica, namely EapB and EapC, have been purified. The corresponding structural genes were isolated by screening a cosmid library, and sequenced. Comparison of genomic and cDNA sequences revealed that the eapB and eapC genes contain three and two introns, respectively. The products of the eapB and eapC genes as deduced from the nucleotide sequences, are 268 and 269 residues long, respectively. N-terminal amino acid sequencing data indicates that EapC is synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Among these, pathogenecity related genes eapB and eapC, encoding two acid proteases (Jara et al, 1996), cpc-1, encoding general amino acid control transcriptional activator (Wang et al, 1998), and a gene whose product was homologous to the carboxypeptidase Y precursor of Candida albicans (Mukhtar et al, 1992), were highly expressed in the CP-M library relative to CP-S library. It was also noted that virus infection altered a dozen of these genes at sporulation stage as revealed by the comparison of EP155-S and EP713 libraries.…”
Section: Gene Expression Patterns At Mycelial and Sporulation Stagesmentioning
confidence: 98%
See 2 more Smart Citations
“…Among these, pathogenecity related genes eapB and eapC, encoding two acid proteases (Jara et al, 1996), cpc-1, encoding general amino acid control transcriptional activator (Wang et al, 1998), and a gene whose product was homologous to the carboxypeptidase Y precursor of Candida albicans (Mukhtar et al, 1992), were highly expressed in the CP-M library relative to CP-S library. It was also noted that virus infection altered a dozen of these genes at sporulation stage as revealed by the comparison of EP155-S and EP713 libraries.…”
Section: Gene Expression Patterns At Mycelial and Sporulation Stagesmentioning
confidence: 98%
“…These include four genes encoding acid protease A (eapC), cross-pathway control protein 1 (CPC1), mitogene-activated protein kinase (Cpmk1), and G-protein CPGB1 identified previously in C. parasitica (Choi et al, 1995(Choi et al, , 2005Jara et al, 1996;Kasahara and Nuss, 1997;Park et al, 2004;Wang et al, 1998), and 13 genes with high degree of similarity with genes found in Sordariomycetes phytopathogens F. graminearum (Guldener et al, 2006) and M. grisea (Dean et al, 2005). Among the newly identified genes were homologues of ODC1, encoding ornithine decarboxylase, that is necessary for wheat infection by the wheat pathogen Stagonospora nodorum (Bailey et al, 2000) and FOW1, encoding a mitochondrial carrier protein, which is required specifically for colonization in the plant tissue by F. oxysporum (Inoue et al, 2002).…”
Section: Pathogenecity Related Genes In C Parasiticamentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, all six are changed in both G-protein-deleted mutants (all are downregulated), but only two are similarly altered in the presence of hypovirus. Previous studies have demonstrated that null mutants of EapA and EapC produced altered extracellular proteolytic profiles, with EapA contributing 97 % of the proteolytic activity detected in C. parasitica culture medium (Jara et al, 1996;Razanamparany et al, 1992). However, information concerning the virulence of these strains is presently unavailable.…”
Section: Potentially Important Signalling Proteins That May Representmentioning
confidence: 99%
“…The characterized proteins known to be part of the G1 family are aspergilloglutamic peptidase (AGP) from Aspergillus niger [4], scytalidoglutamic peptidase (SGP) from Scytalidium lignicolum [5], acid peptidases B and C (EapB and EapC) from Cryphonectria parisitica [6], Penicillium marneffei acid proteinase (PMAP-1) [7], Talaromyces emersonii glutamic peptidase 1 (TGP1) [8] and BcACP1 from Botryotinia fuckeliana [9]. …”
Section: Introductionmentioning
confidence: 99%